Prevalence of anemia in children aged 6 months to 15 years: a hospital based study (Journal of Pathology of Nepal, 2017)
Background: Anemia is a common problem in small children and in adolescents in Nepal. We conducted this study to estimate the prevalence of anemia in hospitalized children in our setup.Materials and Methods: Children aged 6 months to 15 years with hemoglobin < 11 gm/dl were enrolled.  Clinical details of patients including the demographic characteristics, anthropometry, final diagnosis and laboratory results were recorded and retrieved for analysis.Results: Prevalence of anemia was 42.3%. Mean hemoglobin was 9.51 gm/dl. Anemia was more common in children more than five years (53.3%). 73.3% had mild, 20.9% had moderate and 5.7% had severe anemia. Grade I malnutrition was seen in 24.8%, Grade II in 20.9% and grade III in 5.7%. Pneumonia was seen more commonly in children with mild and moderate anemia.Conclusion: Anemia is a common problem in children and may be associated with respiratory infections.